2015
DOI: 10.1037/dev0000020
|View full text |Cite
|
Sign up to set email alerts
|

Child exposure to serious life events, COMT, and aggression: Testing differential susceptibility theory.

Abstract: Both genetic and environmental factors contribute to individual differences in aggression. Catechol-Omethyltransferase Val158Met (COMT), a common, functional polymorphism, has been implicated in aggression and aggression traits, as have childhood experiences of adversity. It is unknown whether these effects are additive or interactional and, in the case of interaction, whether they conform to a diathesis-stress or differential susceptibility model. We examined Gene ϫ Environment interactions between COMT and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 59 publications
6
31
0
2
Order By: Relevance
“…Over the past decade, numerous reports have appeared documenting such GϫE interplay (e.g., Babineau et al, 2015;Bresin, Sima Finy, & Verona, 2013;Brown et al, 2013;Hygen et al, 2015;Hygen, Guzey, Belsky, Berg-Nielsen, & Wichstrøm, 2014); however, the GϫE field has been subjected to controversy and critique (e.g., Duncan & Keller, 2011). Nevertheless, prior research indicates that the OXTR SNP rs53576 interacts with various environmental factors in predicting diverse behavioral and psychological phenotypes.…”
Section: Gene-؋-environment Interactionmentioning
confidence: 99%
“…Over the past decade, numerous reports have appeared documenting such GϫE interplay (e.g., Babineau et al, 2015;Bresin, Sima Finy, & Verona, 2013;Brown et al, 2013;Hygen et al, 2015;Hygen, Guzey, Belsky, Berg-Nielsen, & Wichstrøm, 2014); however, the GϫE field has been subjected to controversy and critique (e.g., Duncan & Keller, 2011). Nevertheless, prior research indicates that the OXTR SNP rs53576 interacts with various environmental factors in predicting diverse behavioral and psychological phenotypes.…”
Section: Gene-؋-environment Interactionmentioning
confidence: 99%
“…Hygen et al found that, given a history of more serious life events, the high activity rs4680 genotype (GG) was associated with more aggression in children at a mean age of 54.8 months. 73 These findings indicate there is a greater susceptibility to poor behavioral outcomes in response to environmental adversity in children with the rs4680 COMT GG genotype. 73 Additionally, carriers of the low activity COMT rs4680 genotype (AA) perform better on tasks of dual cognitive load 74 and have increased cognitive flexibility when exposed to early childhood maltreatment 75 , as compared to other rs4680 genotypes.…”
Section: Discussionmentioning
confidence: 93%
“…73 These findings indicate there is a greater susceptibility to poor behavioral outcomes in response to environmental adversity in children with the rs4680 COMT GG genotype. 73 Additionally, carriers of the low activity COMT rs4680 genotype (AA) perform better on tasks of dual cognitive load 74 and have increased cognitive flexibility when exposed to early childhood maltreatment 75 , as compared to other rs4680 genotypes. These findings confirm the importance of considering the combined effects of genetic and environmental factors on long-term outcomes after traumatic injuries in children.…”
Section: Discussionmentioning
confidence: 93%
“…Although genetic tests cannot currently confirm a psychiatric diagnosis (except in the case of rare genetic syndromes) [31], and the polygenic nature of most psychiatric disorders will likely limit the predictive power of genetic results, studies to identify other genetic links to psychiatric disorders and their interaction with genetic and environmental factors are underway [13, 32]. As it seems likely that psychiatric genetic data will continue to emerge and all but inevitable that such data will be introduced in family courts, it is important to consider their possible implications for child custody evaluators and judicial actors.…”
Section: Psychiatric Genetic Data: Emerging Trends and Knowledgementioning
confidence: 99%